THE DECLINE IN MARRIAGE RATES DUE TO THE PHENOMENON OF CAREER WOMEN FROM THE PERSPECTIVE OF ISLAMIC FAMILY LAW (CASE STUDY IN SAMBOGUNUNG VILLAGE, DUKUN DISTRICT, GRESIK REGENCY) - Shulhah, Rodhiyatus; Faizah, Nur; Velayati, Naili (Al Hakam : The Indonesian Journal of Islamic Family Law and Gender Issues, 2025)
Social phenomena such as childfree, waithood, and unmarried women indicate a shift in societal views on marriage. The increasing role of women in the workforce in Sambogunung Village has resulted in a decrease in the number of marriages, with many women choosing to postpone marriage in order to achieve financial independence and develop themselves. This shift in the perspective of the more educated younger generation indicates that marriage is no longer seen as an end in itself, but rather as a decision that should be made based on readiness and mutual agreement. Although marriage is still considered important from a social and religious perspective, challenges arise related to family and community stability, including imbalances in gender interactions. On the other hand, this phenomenon also creates opportunities to build more balanced families, where couples can support each other in financial management and domestic responsibilities. Therefore, supporting women in achieving career success is crucial, so that harmonious family values can be maintained and society can adapt to these changes without losing its identity.